Optimisation of farm income in carp culture - application of linear programming technique - Jeyaraman, R (Indian Journal of Fisheries, 2011)
Farmers are considered profit maximizers hence optimization of farm income becomes the utlimate objective. Rice farming is becoming less profitable and therefore fish culture has attracted farmers in farm production diversification. Farmers need information on the optimal combination of the different farming sub-sytems for adoption. This note describes application of Linear Programming Technique for optimization of income in integrated rice-fish-duckvegetable farming system. Results of the study revealed that farm income increased from Rs. 6,739 in pure rice crop farm to Rs. 16,484 in the integrated rice-fish-duck-vegetable farming system. Besides 90-100 mandaysof employment were generated additionally, farm business risk reduced by 17.46 % and farm income was optimised and stabilised